Late onset periprosthetic joint infection of the knee caused by Streptococcus anginosus. Case presentation and literature review - Marongiu, Giuseppe; Conte, Marco; Verderosa, Vincenzo; Congia, Stefano; Dessì, Giuseppe; Verona, Marco; Mazzarello, Vittorio; Donadu, Matthew Gavino (The Journal of Infection in Developing Countries, 2021)
Periprosthetic joint infection (PJI) is one of the most dramatic complications of joint arthroplasty. Although streptococcal bone and joint infections are less common than staphylococcal cases, their role as causative agents of bone and joint remains significant accounting for at least 10% of PJIs. Streptococcus anginosus group (SAG) bacteria are usually found in the normal flora of the urogenital tract, intestinal tract and oropharynx and could cause pyogenic infections to affect brain, lungs and liver. SAG bacteria are uncommonly reported as a cause of osteomyelitis and the involvement of a joint represent a rare event. S. anginosus has been anecdotical related to implant devices infections such as vascular prosthesis or orthopedic implants, however, PJI of the knee has never been fully reported before. We describe the case of a late onset periprosthetic knee infection due to Streptococcus anginosus successfully treated by a two-stage revision arthroplasty and postoperative parenteral Vancomycin, (2 g per day) and Levofloxacin (750 mg per day) for 4 weeks and then oral Levofloxacin for a further 2 weeks.